Response of runoff processes to temperature rise in basins with different glacier ratios in the monsoon-influenced southern Tibetan Plateau - Wang, L.; Zhang, F.; Nepal, Santosh; Xiang, Y.; Tang, H.; Shi, X.; Zeng, C.; Ahmad, I.; Yu, Z. (Elsevier, 2023)
Study region: River basins with glacier ratios ranging from 1.8% to 20.7% in the monsoon-influenced southern Tibetan Plateau. Study focus: The response of runoff processes in basins with different glacier ratios under global warming of 1.5 C and 2 C was explored based on SPHY (Spatial Processes in Hydrology) model and GCMs (General Circulation Models). New hydrological insights for the region: More prominent temperature and precipitation changes were observed in the monsoon-influenced southern Tibetan Plateau compared with the global averages. With increasing temperature and precipitation, the total runoff and glacier runoff of these basins showed increasing trends under global warming of 1.5 C and 2 C. Compared with the baseline period (1985–2014), increases were observed in the total runoff (1.7–20.6%), base flow (2.8–8.3%), glacier runoff (8.1–35.9%), and rainfall runoff (6.0–36.0%) of these basins. In contrast, snowmelt runoff decreased (- 28.3% - - 4.3%). Therefore, relevant management and allocation of water resources may be required. The hydrological regulation function of glaciers was found to be strongly correlated with glacier ratio. In general, the hydrological regulation function of glaciers would decrease in the future along with warming induced glacier retreat. These findings would help deepen the understanding of runoff processes on the Tibetan Plateau and other alpine regions, thus providing a scientific basis for water resources management under climate change.